Zmynd17 controls muscle mitochondrial quality and whole‐body metabolism. Issue 9 (13th April 2018) - Fujita, Ryo; Yoshioka, Kiyoshi; Seko, Daiki; Suematsu, Takashi; Mitsuhashi, Satomi; Senoo, Nanami; Miura, Shinji; Nishino, Ichizo; Ono, Yusuke
ABSTRACT: Muscle mitochondria are crucial for systemic metabolic function, yet their regulation remains unclear. The zinc finger MYND domain‐containing protein 17 (Zmynd17) was recently identified as a muscle‐specific gene in mammals. Here, we investigated the role of Zmynd17 in mice. We found Zmynd17 predominantly expressed in skeletal muscle, especially in fast glycolytic muscle. Genetic Zmynd17 inactivation led to morphologic and functional abnormalities in muscle mitochondria, resulting in decreased respiratory function. Metabolic stress induced by a high‐fat diet upregulated Zmynd17 expression and further exacerbated muscle mitochondrial morphology in Zmynd17 ‐deficient mice. Strikingly, Zmynd17 deficiency significantly aggravated metabolic stress‐induced hepatic steatosis, glucose intolerance, and insulin resistance. Furthermore, middle‐aged mice lacking Zmynd17 exhibited impaired aerobic exercise performance, glucose intolerance, and insulin resistance. Thus, our results indicate that Zmynd17 is a metabolic stress‐inducible factor that maintains muscle mitochondrial integrity, with its deficiency profoundly affecting whole‐body glucose metabolism.—Fujita, R., Yoshioka, K., Seko, D., Suematsu, T., Mitsuhashi, S., Senoo, N., Miura, S., Nishino, I., Ono, Y. Zmynd17 controls muscle mitochondrial quality and whole‐body metabolism. FASEB J. 32, 5012–5025 (2018). www.fasebj.org